Kaling Village Youth Generation Business Workshop In Kaling District Tasikmadu Karanganyar - Agus Suyatno; Khabib Alia Akhmad (VSJ | Veteran Society : Jurnal Pengabdian Masyarakat, 2021)
The government has carried out overcoming the problem of unemployment by launching the entrepreneurial movement. However, strengthening the movement by incorporating it into the learning curriculum is less effective because the educational target is only focused on the cognitive domain in the form of elaborating the theory of entrepreneurship without being followed by concrete steps. The translation of theory into the real world needs to be done quite well. Entrepreneurship training will be able to describe knowledge in the theoretical realm more focused on the practical realm. Many potential creative ideas to run a business have not been explored optimally. Among the people of Kaling Village, guidance activities are directed towards positive religious activities. This type of coaching directs participants to fill their spare time between work and school to learn religious concepts and theories in several aspects. The growth of an entrepreneurial spirit is also able to provide benefits to the community. These benefits can be in the form of financial and non-financial benefits. The financial benefits of entrepreneurship can be in the form of economic independence obtained in running a business. While the non-financial benefits are in the form of mental growth that is tough and never gives up in dealing with life's problems. Entrepreneurship training for the community, especially the younger generation, to foster an entrepreneurial spirit and explore existing potential. By holding entrepreneurship training, it is hoped that it will be able to create new businesses and have a positive effect on the mental development of the younger generation's independence. This training is aimed at the younger generation being assisted by the Karang Taruna Kaling Village.